A review on decision-making methods in engineering design for the automotive industry. (1st February 2017) - Renzi, Cristina; Leali, Francesco; Di Angelo, Luca
ABSTRACT: Decision-making methods have proven to be an effective support to engineering design. However, it is proved that very often designers prefer tested procedures and experience-based approaches. Many reasons have been discussed in the literature, dealing with consolidated design habits of people and companies, high cost in terms of time consumption, and lack of tools and knowledge. The paper systematically investigates, through an extended critical review, how decision-making methods can be used by automotive designers to solve the most common engineering problems involved along the design process. In particular, the paper proposes an original classification of the most widely used decision-making methods in engineering design, a match between such techniques with the typical design phases, and a mapping of their application into the automotive field. This research can be considered as a further step to transfer the state-of-the-art knowledge on decision-making methods to the industrial context, establishing a common background for practitioners and researchers.